1) 3(3-x)+2x+8-2(x-1)
3) 4x+5-(3x+6)=2(2+x)-4
5) 4-2(5-x)=x-4(x-1)
7) 2(2x-3)+3(4-x)=-(x+1)
9) 6(x-1)+3(2-x)=2(2x-1)-(4-x)
11) 3(x-4)-2(3-2x)=-(3x-1)-(1-x)
13) 1-2(x-3)-(3x+5)=-x-(2x-1)+2

Musi być koniecznie rozpisane.
Z góry dziękuje.


Odpowiedź :

1) 3(3-x)+2x+8-2(x-1)= 9-3x+2x+8-2x+1=18-3x


3) 4x+5-(3x+6)=2(2+x)-4=4x+5-3x-6=4+2x= -2x=-5
x=2,5



5) 4-2(5-x)=x-4(x-1)=4-10+2x=-3x+4= -5x=10
x=-2


7) 2(2x-3)+3(4-x)=-(x+1)= 4x-6+12-3x=-x-1= 2x=5
x=2,5


9) 6(x-1)+3(2-x)=2(2x-1)-(4-x)=6x-6+6-3x=4x-2-4+x= -2x=-6
x=3


11) 3(x-4)-2(3-2x)=-(3x-1)-(1-x)=3x-12-6+4x=-3x+1-1+x= 9x=18
x=2


13) 1-2(x-3)-(3x+5)=-x-(2x-1)+2=1-2x+6-3x-5=-x-2x+1+2= -2x=1
x= -0,5

Pozdrawiam ;)
1) 3(3-x)+2x+8-2(x-1)=9-3x+2x+8-2x+2=-3x+19
3) 4x+5-(3x+6)=2(2+x)-4 4x+5-3x-6=4+2x 4x-3x-2x=-5+6+4 -x=5 x=-5
5) 4-2(5-x)=x-4(x-1) 4-10+2x=x-4x+4 2x-x+4x=4-4+10 5x=10/5 x=2
7) 2(2x-3)+3(4-x)=-(x+1) 4x-6+12-3x=-x-1 4x-3x+x=-1+6-12 2x=-7/2 x=-3 1/2
9) 6(x-1)+3(2-x)=2(2x-1)-(4-x) 6x-6+6-3x=4x-2-4+x 6x-3x-4x-x=-2-4+6-6 -2x=-6/(-2) x=3
11) 3(x-4)-2(3-2x)=-(3x-1)-(1-x) 3x-12-6+4x=-3x+1-1+x 3x+4x+3x-x=1-1+12+6 9x=18/9 x=2
13) 1-2(x-3)-(3x+5)=-x-(2x-1)+2 1-2x+6-3x-5=-x-2x+1+2 -2x-3x+x+2x=1+2-1-6+5 -2x=1/(-2) x=-1/2
3(3-x)+2x+8-2(x-1)
9-3x+2x=8-2x+1
-3x+2x+2x=9+8+1
x=0

4x+5-(3x+6)=2(2+x)-4
4x+5-3x-6=4+2x-4
4x-3x-2x=-5+6+4-4
-x=1|:-1
x=-1

5) 4-2(5-x)=x-4(x-1)
-10+2x=x-4x
2x-x+4=10
5x=10|:5
x=2

7) 2(2x-3)+3(4-x)=-(x+1)
4x-6+12-3x=-x-1
4x-3x+x=6-12-1
x=2,5

9) 6(x-1)+3(2-x)=2(2x-1)-(4-x)
6x+6+6-3x=4x-2-4+x
6x-3x-4x-x=-6-6-2-4
-2x=-18|:-2

11) 3(x-4)-2(3-2x)=-(3x-1)-(1-x)
3x-12-6+4x+-3x+1-1+x
3x+4x+3x-x=12+6+1-1
9x=18|:9
x=2

13) 1-2(x-3)-(3x+5)=-x-(2x-1)+2
1-2x+6-3x-5=-x-2x+1+2
2x-3x+x+2x=-1-6+5+1+2
2x=2|:2
x=1